Foliar trichome variations in 49 accessions of Solanum aethiopicum (Solanaceae) - LAILANI A. MASUNGSONG; MARIA CELESTE N. BANATICLA-HILARIO; NONNATUS S. BAUTISTA; LERMA SJ. MALDIA; NELSON M. PAMPOLINA; INOCENCIO E. BUOT JR. (Society for Indonesian Biodiversity, 2026)
Abstract. Masungsong LA, Banaticla-Hilario MCN, Bautista NS, Maldia LS, Pampolina NM, Buot Jr. IE. 2026. Foliar trichome variations in 49 accessions of Solanum aethiopicum (Solanaceae). Biodiversitas 27 (2): d270221. https://doi.org/10.13057/biodiv/d270221. Trichomes are essential micromorphological structures that mediate plant-environment interactions. Although trichome diversity has been extensively documented across the genus Solanum, available information for Solanum aethiopicum remains limited. This study aimed to investigate foliar trichomes in 49 accessions from Hortanova Farm and Research Center, Eastwest Seed Company, Inc., in Lipa City, Batangas, Philippines, to characterize their morphology, classify trichome types, and analyze patterns of intraspecific variation. Observations were performed using light microscopy (200x magnification), supported by standardized morphometric and structural criteria. A diagnostic dichotomous key was subsequently developed to aid in identification. Ten distinct trichome types were recognized, consisting of glandular (Types 3 and 6) and non-glandular forms (Types 1, 2, 4, 5, 7, 8, 9, and 10). Stellate trichomes were dominant, and four newly described stellate types (Types 7, 8, 9, and 10) were reported. Among these, Type 9, a non-glandular stellate trichome with straight radial rays, appeared consistently across all accessions and emerged as a robust diagnostic feature, whereas Types 1 and 2 occurred only in specific accessions, indicating potential trait exclusivity. The widespread distribution of Type 9 and contrasting morphological differences suggest adaptive significance. These findings expand micromorphological knowledge and present taxonomic implications for S. aethiopicum.